Development Model of Food Crop in Suboptimal Area Based on Farmers Corporation in Ogan Ilir Regency, South Sumatra - Riswani Riswani; Yunita Yunita; Henny Malini; Thirtawati Thirtawati (Research Center for Sub-optimal Lands (PUR-PLSO), Universitas Sriwijaya, 2021)
This research was conducted based on the condition of fulfilling the food needs of the region, which was currently not being carried out with the distribution pattern and weak institutional Strengtening at the farmer level, so that its utilization was not yet efficient in exploitation especially on suboptimal land. Based on this, the main objective of this study was to formulate a model for the development of food crop agricultural areas on suboptimal land oriented to farmer corporations. This research used qualitative methods but the relevant mathematical formulas were still used. From the result of the analysis, an applicative program for the development of agricultural areas based on farmer corporation in Ogan Ilir Regency was compiled, which was based on a political, technocratic approach, integration of top down policy-bottom up planning and participatory. The recommended program group was divided into programs for optimizing the availability of production inputs, developing rice cultivation and supporting infrastructure, controlling pests and diseases of rice plants, improving and empowering farmer institutions, improving and increasing farmers' knowledge and skills, improving harvest and post-harvest, improving marketing, improvement of supporting infrastructure, and development of capital. The location for the development and implementation of the program was focused on the districts of Muara Kuang, Pemulutan, Lubuk Keliat, Indralaya and Pemulutan Selatan.